2011
DOI: 10.1007/s00221-011-2606-2
|View full text |Cite
|
Sign up to set email alerts
|

Visually triggered K-complexes: a study in New Zealand rabbits

Abstract: K-complexes are the EEG elements recorded during the state of developing sleep and during slow wave sleep. They are the only EEG components which can be elicited by sensory stimulation during sleep. The peculiarity of New Zealand rabbits to sleep with their eyes open allows the use of visual stimuli to elicit K-complexes. Experiments were performed with three rabbits. For visual stimulation, an elongated screen illuminated by LED flashes was attached to an implant on the animal's skull. The screen covered 20-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…This wake-like sleep posture may explain why sleep is rarely reported in studies on time budgets and activity patterns in wild ostriches [27], [28]. SWS with open eyes has been reported in other avian [29][32] and mammalian [33], [34] species, and may allow for visual processing concurrent with sleep [32], [35]. During SWS, the EEG showed slow waves (Figure 2A, Figure S1) like those recorded from other birds engaged in SWS [36][38].…”
Section: Resultsmentioning
confidence: 98%
“…This wake-like sleep posture may explain why sleep is rarely reported in studies on time budgets and activity patterns in wild ostriches [27], [28]. SWS with open eyes has been reported in other avian [29][32] and mammalian [33], [34] species, and may allow for visual processing concurrent with sleep [32], [35]. During SWS, the EEG showed slow waves (Figure 2A, Figure S1) like those recorded from other birds engaged in SWS [36][38].…”
Section: Resultsmentioning
confidence: 98%
“…In discussion of cortical visceral activation during sleep one often argues that these visceral responses can be of non-specific origin resembling sensory triggered K-complexes. This question was investigated in details in our recent study 55 where it was shown that visually induced K-complexes had absolutely specific origin. In addition, K-complexes could be induced by sensory stimuli only during short interval of developing sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical visceral responses on the contrary could be recorded during periods of deep slow-wave sleep when K-complexes could not be induced by any sensory stimulation. In our study of the induced K-complexes 55 we presented the arguments, which indicated that visually induced K-complexes also may reflect excitation coming from the visceral systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the subliminal process might work as a system that compensates for the decline seen in the level of consciousness with strong sleepiness, a situation that poses considerable danger to survival. For example, as a prey animal, a certain rabbit species sleeps with their eyes open in the wild, during which time their electroencephalograms show brain activation due to visual stimuli [18]. This is advantageous because it enables the animals to respond quickly to an attack by natural enemies, by waking up and engaging in avoidance behavior.…”
Section: Introductionmentioning
confidence: 99%